The Little Book of Insider Dealing. - Durston, Gregory (Waterside Press, 2018)
Suitable for beginners and practitioners alike. The first concise treatment and highly topical. A gem for finance industry professionals, lawyers and students as well as ordinary investors (who like everyone else must avoid putting themselves at risk).